Temperature Field and Gradient Effect of a Steel-Concrete Composite Box Girder Bridge. (10th September 2021) - Li, Haoxu; Zhang, Zhiguo; Deng, Nianchun
Abstract : To study the effect of the temperature field and gradient of a steel-concrete composite box girder bridge, a 5 × 35 continuous composite box girder bridge is used as the research object. The temperature measuring point is set by selecting a typical cross section, and the temperature change data are measured. The temperature field of the different positions in the composite box girder bridge is studied, the global and local temperature differences are compared, and the law of temperature distribution and the main factors affecting the temperature field are formulated. The most unfavourable expression function of the vertical temperature gradient of the section is simulated using the measured data, the existing standard temperature gradient mode is compared, the finite element model of the bridge is established, and the influence of the actual temperature gradient mode on the stress and deformation of the composite girder is further analysed. The conclusions show that the temperature differences of different azimuth sections and the local temperature differences between the steel and concrete joint parts of the steel-concrete composite box girder bridge are not significant. The temperature gradient heating and cooling model fitted by the measured temperature field can be used as a reference for the structural design of similar local bridges.